Assessing alexithymia: the proposal of a psychometric tool based on spheric videos - Simoncini, Gloria; Borghesi, Francesca; Mancuso, Valentina; Pedroli, Elisa; Cipresso, Pietro (Frontiers in Human Neuroscience, 2024)
The present perspective introduces a novel psychometric tool designed to enhance the evaluation of alexithymia. Alexithymia, a condition marked by difficulties in recognizing and expressing emotions, along with a propensity to direct attention outside rather than towards one's own interior experiences, is commonly investigated through self-report questionnaires. These instruments assume that individuals have sufficient self-awareness and abstraction capabilities, which restricts the understanding of the underlying mechanisms of emotional recognition in individuals who do not possess these capacities. To address this lack, emerging technologies like virtual reality (VR) and 360° videos facilitate the recreation of immersive contexts, enabling subjects to engage with scenarios even remotely. Our innovative tool employs spherical video technology to recreate social and non-social scenarios that elicit emotions. Psychophysiological measures are collected during video observation; then, questions are asked to investigate how the subject consciously processes the emotions they experienced. This multimodal approach aims to capture both implicit and explicit emotion processing, providing a comprehensive assessment. Overall, the proposed psychometric tool offers the potential for a more nuanced understanding of alexithymic traits and their real-life impact, empowering clinicians to tailor treatment processes to individual needs based on a richer set of information.